Imaging findings of hepatosplenic schistosomiasis: A case report - Bilgin, Sabriye Şennur; Toprak, Hüseyin; Şeker, Mehmet Metin (Elsevier Inc, 2016)
In our study, in a 52-year-old man, specific and nonspecific findings of Schistosoma infestation were examined using ultrasonography, computed tomography, and magnetic resonance imaging. On computed tomography, capsular and septal calcifications and contrast enhancement of the liver capsule were seen. On T1-weighted magnetic resonance images diffuse hypointensity was seen in periportal spaces; on T2-weighted images in the same spaces, diffuse hyperintensity was seen. On dynamic contrast-enhanced T1-weighted images, in these same spaces marked contrast enhancement was manifested in the late venous phase. These signal changes indicate edema due to periportal fibrotic tissue inflammation and are accepted as pathognomonic for a liver infested by Schistosoma.
Keywords: CT; Hepatosplenic Schistosomiasis; MRI